2019
DOI: 10.4049/jimmunol.1900383
|View full text |Cite
|
Sign up to set email alerts
|

Teleost Gasdermin E Is Cleaved by Caspase 1, 3, and 7 and Induces Pyroptosis

Abstract: Pyroptosis is a newly defined gasdermin (GSDM)-dependent inflammatory type of programmed cell death. Different from mammals, which have a panel of pyroptotic GSDM members (e.g., GSDMA-E), teleosts possess only GSDME. The pyroptotic activity and regulation mechanism of teleost GSDME remain to be elucidated. In this work, we investigated the activity of the teleost Cynoglossus semilaevis (tongue sole) GSDME (CsGSDME) in association with different caspases (CASPs). We found that CsGSDME exerted pyroptotic and bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 58 publications
(52 reference statements)
3
61
0
Order By: Relevance
“…Caspase-1 cleaves a 50-kD gasdermin D to a 29-kD pore forming N-terminus fragment, which is inserted into the plasma membrane causing membrane leakage and cell death by pyroptosis (Dubois et al, 2019). Recently, a role for gasdermine E in pyroptosis was implicated (Jiang et al, 2019); therefore, we will perform further studies on the role of caspase-1 and gasdermin isoforms in pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 cleaves a 50-kD gasdermin D to a 29-kD pore forming N-terminus fragment, which is inserted into the plasma membrane causing membrane leakage and cell death by pyroptosis (Dubois et al, 2019). Recently, a role for gasdermine E in pyroptosis was implicated (Jiang et al, 2019); therefore, we will perform further studies on the role of caspase-1 and gasdermin isoforms in pyroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is formed by a receptor (NOD-like receptor (NLR) family or non-NLR (AIM2)), an adapter protein (ASC, apoptosis-associated specklike protein containing a CARD) and CASP1 that cleaves pro-IL18, pro-IL1β and GSDM. However, it is now clear that pyroptosis can also be activated by other caspases such as CASP3 [90] ( Figure 2). The recent description of necroptosis and pyroptosis processes has amplified the complexity of RCD understanding.…”
Section: Inflammasome Activation and Pyroptosismentioning
confidence: 99%
“…Cas1 mRNA levels were upregulated, but it was not accompanied or followed by an upregulation of il1β mRNA levels. Cas1 upreglation could have played a role in pyroptosis, a gasdermin (GSDM)-dependent inflammatory type of programmed cell death (69). Different from mammals, which have a panel of pyroptotic GSDM members (e.g., GSDMA-E), teleosts only possess GSDME.…”
Section: Figure 5 |mentioning
confidence: 99%
“…Different from mammals, which have a panel of pyroptotic GSDM members (e.g., GSDMA-E), teleosts only possess GSDME. Jiang et al (69) found that teleost GSDME exerted pyroptotic activity and bactericidal activities through its N-terminal domain. GSDME is specifically and highly efficiently cleaved by teleost caspase 1, releasing the N-terminal domain.…”
Section: Figure 5 |mentioning
confidence: 99%